Pediatric rehabilitation principles and practice - Houtrow, Amy; McMahon, Mary A.; Murphy, Kevin P. 1956- (Springer Publishing Company, LLC, 2021)
This revised and greatly expanded sixth edition of Pediatric Rehabilitation continues to set the standard of care for clinicians and remains the premier reference dedicated to education and training in the field of pediatric rehabilitation medicine. Under the direction of a new editorial team, this text brings together renowned specialists from all sectors of the pediatric rehabilitation community to provide the most current and comprehensive information with evidence-based discussions throughout. The sixth edition encompasses substantial updates from beginning to end and addresses emerging topics in the field with eight entirely new chapters devoted to brachial plexus palsy, oncology, robotics, genetics, spasticity management, rheumatology, burns, and advocacy. Major revisions to chapters on spinal cord injuries, acquired brain injury, cerebral palsy, neuromuscular diagnoses, and medical care of children reflect recent advances and expand coverage to include pediatric stroke, anoxic brain injury, bone health, pain management, and more. Chapter pearls, detailed summary tables, and over 250 figures emphasize major takeaways from the text for readers. With contributors chosen both for their academic and clinical expertise, chapters offer a real hands-on perspective and reference the most up to date literature available"--